Learning culture and language through ICTs [ methods for enhanced instruction - Chang, Maig , 1974-; Kuo, Chen-Wo (Information Science Reference, 2009)
"This book offers readers an authoritative reference to the current progress of Chinese language and cultural e-learning"--Provided by publisher